Educational practice as a tool in the formation of professional competence of future primary education teachers - Yusupov M.M (Research Parks Publishing LLC, 2021)
This article is aimed at the essence, content, methods and forms of organization of training and internships in higher education institutions, as well as the formation of professional competence